Epidermal Cyst of Parotid Gland: A Rarity and a Diagnostic Dilemma - Anuradha Ganesan; Gautham Kumar Nandakumar (Case Reports in Dentistry)
Epidermal cysts are common skin lesions but they occur very rarely in the oral cavity, especially in the salivary glands. Very few cases have been reported in the literature and, here, we present one such rare case of epidermal cyst in the right parotid gland in a 62-year-old female patient.